Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's consider the given conditions. We have [tex]\( p = \text{True} \)[/tex] (T) and [tex]\( q = \text{False} \)[/tex] (F).
The expressions to evaluate are:
1. [tex]\( p \rightarrow q \)[/tex]
2. [tex]\( q \rightarrow p \)[/tex]
3. [tex]\( \sim p \rightarrow \sim q \)[/tex]
4. [tex]\( \sim q \rightarrow \sim p \)[/tex]
We apply the definitions of each logical implication:
- The implication [tex]\( p \rightarrow q \)[/tex] is equivalent to [tex]\( \sim p \lor q \)[/tex].
- The implication [tex]\( q \rightarrow p \)[/tex] is equivalent to [tex]\( \sim q \lor p \)[/tex].
- The implication [tex]\( \sim p \rightarrow \sim q \)[/tex] is equivalent to [tex]\( p \lor \sim q \)[/tex].
- The implication [tex]\( \sim q \rightarrow \sim p \)[/tex] is equivalent to [tex]\( q \lor \sim p \)[/tex].
Given that [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{False} \)[/tex], we substitute these values into the above expressions:
1. [tex]\( p \rightarrow q \)[/tex]: This is [tex]\( \sim p \lor q \)[/tex]. Since [tex]\( p \)[/tex] is True, [tex]\( \sim p \)[/tex] is False. Thus, [tex]\( \sim p \lor q \)[/tex] becomes False [tex]\(\lor\)[/tex] False, which is False. So, [tex]\( p \rightarrow q \)[/tex] is False.
2. [tex]\( q \rightarrow p \)[/tex]: This is [tex]\( \sim q \lor p \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True. Thus, [tex]\( \sim q \lor p \)[/tex] becomes True [tex]\(\lor\)[/tex] True, which is True. So, [tex]\( q \rightarrow p \)[/tex] is True.
3. [tex]\( \sim p \rightarrow \sim q \)[/tex]: This is [tex]\( p \lor \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True. Thus, [tex]\( p \lor \sim q \)[/tex] becomes True [tex]\(\lor\)[/tex] True, which is True. So, [tex]\( \sim p \rightarrow \sim q \)[/tex] is True.
4. [tex]\( \sim q \rightarrow \sim p \)[/tex]: This is [tex]\( q \lor \sim p \)[/tex]. Since [tex]\( p \)[/tex] is True, [tex]\( \sim p \)[/tex] is False. Thus, [tex]\( q \lor \sim p \)[/tex] becomes False [tex]\(\lor\)[/tex] False, which is False. So, [tex]\( \sim q \rightarrow \sim p \)[/tex] is False.
Therefore, we can complete the table as follows:
\begin{tabular}{|c|c|c|c|c|c|}
\hline
[tex]$p$[/tex] & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$q \rightarrow p$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] & [tex]$\sim q \rightarrow \sim p$[/tex] \\
\hline
T & F & F & T & T & F \\
\hline
\end{tabular}
The expressions to evaluate are:
1. [tex]\( p \rightarrow q \)[/tex]
2. [tex]\( q \rightarrow p \)[/tex]
3. [tex]\( \sim p \rightarrow \sim q \)[/tex]
4. [tex]\( \sim q \rightarrow \sim p \)[/tex]
We apply the definitions of each logical implication:
- The implication [tex]\( p \rightarrow q \)[/tex] is equivalent to [tex]\( \sim p \lor q \)[/tex].
- The implication [tex]\( q \rightarrow p \)[/tex] is equivalent to [tex]\( \sim q \lor p \)[/tex].
- The implication [tex]\( \sim p \rightarrow \sim q \)[/tex] is equivalent to [tex]\( p \lor \sim q \)[/tex].
- The implication [tex]\( \sim q \rightarrow \sim p \)[/tex] is equivalent to [tex]\( q \lor \sim p \)[/tex].
Given that [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{False} \)[/tex], we substitute these values into the above expressions:
1. [tex]\( p \rightarrow q \)[/tex]: This is [tex]\( \sim p \lor q \)[/tex]. Since [tex]\( p \)[/tex] is True, [tex]\( \sim p \)[/tex] is False. Thus, [tex]\( \sim p \lor q \)[/tex] becomes False [tex]\(\lor\)[/tex] False, which is False. So, [tex]\( p \rightarrow q \)[/tex] is False.
2. [tex]\( q \rightarrow p \)[/tex]: This is [tex]\( \sim q \lor p \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True. Thus, [tex]\( \sim q \lor p \)[/tex] becomes True [tex]\(\lor\)[/tex] True, which is True. So, [tex]\( q \rightarrow p \)[/tex] is True.
3. [tex]\( \sim p \rightarrow \sim q \)[/tex]: This is [tex]\( p \lor \sim q \)[/tex]. Since [tex]\( q \)[/tex] is False, [tex]\( \sim q \)[/tex] is True. Thus, [tex]\( p \lor \sim q \)[/tex] becomes True [tex]\(\lor\)[/tex] True, which is True. So, [tex]\( \sim p \rightarrow \sim q \)[/tex] is True.
4. [tex]\( \sim q \rightarrow \sim p \)[/tex]: This is [tex]\( q \lor \sim p \)[/tex]. Since [tex]\( p \)[/tex] is True, [tex]\( \sim p \)[/tex] is False. Thus, [tex]\( q \lor \sim p \)[/tex] becomes False [tex]\(\lor\)[/tex] False, which is False. So, [tex]\( \sim q \rightarrow \sim p \)[/tex] is False.
Therefore, we can complete the table as follows:
\begin{tabular}{|c|c|c|c|c|c|}
\hline
[tex]$p$[/tex] & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$q \rightarrow p$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] & [tex]$\sim q \rightarrow \sim p$[/tex] \\
\hline
T & F & F & T & T & F \\
\hline
\end{tabular}
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.